Select Phytochemicals Reduce Campylobacter jejuni in Postharvest Poultry and Modulate the Virulence Attributes of C. jejuni - Wagle, Basanta R.; Donoghue, Annie M.; Jesudhasan, Palmy R. (Frontiers in Microbiology, 2021)
Consumption or handling of poultry and poultry products contaminated with Campylobacter species are a leading cause of foodborne illness in humans. Current strategies employed to reduce Campylobacter in live chickens provide inconsistent results indicating the need for an alternative approach. This study investigated the efficacy of phytochemicals, namely turmeric, curcumin, allyl sulfide, garlic oil, and ginger oil, to reduce Campylobacter jejuni in postharvest poultry and sought to delineate the underlying mechanisms of action. Two experiments were conducted on the thigh skin of the chicken, and each experiment was repeated twice. Samples were inoculated with 50 μL (~107 CFU/sample) of C. jejuni strain S-8 and allowed to adhere for 30 min. Skin samples were dipped into their respective pre-chilled treatment solutions (0.25 and 0.5% in experiments 1 and 2, respectively) at 4°C for an hour to simulate chilling tank treatment, followed by plating to enumerate C. jejuni (n=3 samples/treatment/trial). The mechanisms of action(s) were investigated using subinhibitory concentration (SIC) in adhesion, quorum sensing, and gene expression analyses. Adhesion assay was conducted on the monolayers of ATCC CRL-1590 chicken embryo cells challenged with C. jejuni and incubated in the presence or absence of phytochemicals for 1.5 h, followed by plating to enumerate adhered C. jejuni. The effects of phytochemicals on quorum sensing and cell viability were investigated using Vibrio harveyi bioluminescence, and LIVE/Dead BacLight™ bacterial viability assays, respectively. In addition, droplet digital PCR determined the gene expression analyses of C. jejuni exposed to phytochemicals. Data were analyzed by GraphPad Prism version 9. C. jejuni counts were reduced by 1.0-1.5 Log CFU/sample with garlic oil or ginger oil at 0.25% and 0.5% (p<0.05). The selected phytochemicals (except curcumin) reduced the adhesion of C. jejuni to chicken embryo cells (p<0.05). In addition, all the phytochemicals at SIC reduced quorum sensing of C. jejuni (p<0.05). The cell viability test revealed that cells treated with 0.25% of phytochemicals had compromised cell membranes indicating this as a mechanism that phytochemicals use to damage/kill C. jejuni. This study supports that the application of phytochemicals in postharvest poultry would significantly reduce C. jejuni in poultry meat.